Epipericardial fat necrosis as a differential diagnosis of chest pain—A case report. Issue 1 (24th December 2019) - Neto, Ana; Seabra, Daniel; Moreno, Nuno; Magalhães, Sara; Pires, Lindora; Pinto, Paula
Abstract: Epipericardial fat necrosis (EFN) is an uncommon self‐limiting benign condition that can present with substantial chest pain. We present a case of an otherwise healthy 42‐year‐old man who presented with severe chest pain in the emergency department. Initial cardiopulmonary workup was unrevealing. Contrast‐enhanced thorax CT demonstrated an increased radiolucency and nodularity of anterior pericardial fat consistent with epipericardial fat necrosis. The transthoracic echocardiogram was normal, and cardiac magnetic resonance imaging confirmed the lesion. Combined anti‐inflammatory therapy was started with favorable evolution.